The Impact of Organizational Culture on Professional Quality of Life Among Filipino Nurse Educators in the USA - Regachuelo, Edmon (Celebes Nursing Journal, 2025)
Introduction: Organizational culture plays an important role in someone's acclimation to a new environment thus impacting on professional quality of life. Objective: The aim of the study is to determine the influence of organizational culture (nursing culture, perceived organizational support, work engagement) on the professional quality of life among Filipino immigrant’s nurse educators in the USA. Method: The research is a cross-sectional study using a descriptive non-experimental correlational quantitative design; 204 Filipino immigrants nurse educators were chosen using a convenient purposive sampling technique. Moreover, four adapted online questionnaires utilized Nursing Culture Assessment Tool (NCAT), Survey of Perceived Organizational Support (SPOS), Utrecht Work Engagement Scale (UWES-9S) and ProQoL Version V in the study. Result: The demographic profile showed that majority of the Filipino nurse participants belong to middle age groups, mostly female, married, and with master’s degree. Most of the participants have been an educator for less than 10 years, and a full-time nurse educator. Majority of the Filipino nurse educators “agree” with the existence of the six dimensions of nursing culture. Moreover, expectations have the highest influence, followed by teamwork and commitment, however satisfaction is the lowest amongst Filipino nurse educators. Filipino nurse educators perceived the organizational support as “neither agree nor disagree” to which an organization values and supports their contributions and well-being. Conclusion: Majority of the Filipino nurse educators “moderately agree” of their work engagement and involvement. The domains of work engagement showed that dedication has the highest impact, while absorption is the lowest amongst Filipino nurse educators. Majority of the Filipino nurse educators had an “borderline moderate to high” level of compassion satisfaction, “borderline moderate to high” level of compassion fatigue: secondary traumatic stress, and “average or moderate” level of compassion fatigue: burnout